Analysis of MAXIM Application Service Quality on User Satisfaction using the E-Service Quality Method - Wulandari, Putri; Dzakiyullah, Nur Rachman; Ratnasari, Asti; Heksaputra, Dadang (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
Service quality is the comprehensive support provided by system developers to users to ensure safety, comfort, empathy and responsiveness in meeting user expectations. There are still complaints about the Maxim application in the Google Playstore review from January 16 to February 12, 2024, inaccurate pick-up or destination, inconsistent prices, slow service response so that users have difficulty getting solutions to problems. Supported by the INDEF (Institute for Development of Economics and Finance) survey on DataIndonesia.id that the popularity of Maxim's services is lower than Gojek and Grab. Thus, it is essential to employ the E-Servqual approach to perform research to determine whether the services have satisfied users. Because its dimensions are pertinent and completely satisfy the requirements of assessing the quality of electronic services, E-Service Quality is the most thorough and integrative online service quality model. Efficiency, fulfillment, system availability, privacy, responsiveness, compensation, and interaction are the seven factors used, while user satisfaction is the dependent variable. This kind of study collects data using nonprobability sampling approaches in conjunction with quantitative methods. wherein demographic components are chosen according to specific standards that are pertinent to the study's goals. Considering the findings of the analysis, the 7 proposed hypotheses consisted of 3 accepted hypotheses and 4 rejected hypotheses because the significance value < alpha (? = 0.05) and 4 hypotheses rejected because the significance value > alpha (? = 0.05. Overall, the quality of Maxim's service towards user satisfaction is not good in terms of the variables of efficiency, system availability, responsiveness, and contact. It is hoped that there will be improvements in the Maxim application such as application usage, application functions on the displayed page, application response, and contact services for communication